2023
DOI: 10.1097/ju.0000000000003080
|View full text |Cite
|
Sign up to set email alerts
|

Post-diagnostic Zinc Supplement Use and Prostate Cancer Survival Among Men With Nonmetastatic Prostate Cancer

Abstract: Purpose:Biological and experimental evidence support restoration of normal zinc levels in malignant prostate cells as a promising prostate cancer treatment, yet the influence of zinc supplementation after diagnosis on prostate cancer survival in a human population is unknown.Materials and Methods:We prospectively assessed post-diagnostic zinc supplementation in relation to prostate cancer survival among 5,788 men with nonmetastatic prostate cancer in the Health Professionals Follow-up Study (1986-2019). We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, the effects of zinc supplementation are controversial, with results varying significantly according to mechanisms that are not well understood. Some studies have suggested that zinc supplementation may benefit prostate cancer patients by reducing the risk of lethal prostate cancer [107][108][109]. In contrast, recent studies, including a 30-year follow-up study and a multi-case control study in Spain, have indicated that zinc supplementation may increase the risk of lethal and aggressive prostate cancer [18,110].…”
Section: Could the Dysregulation Of Zinc Transporters Affect Zinc Sup...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of zinc supplementation are controversial, with results varying significantly according to mechanisms that are not well understood. Some studies have suggested that zinc supplementation may benefit prostate cancer patients by reducing the risk of lethal prostate cancer [107][108][109]. In contrast, recent studies, including a 30-year follow-up study and a multi-case control study in Spain, have indicated that zinc supplementation may increase the risk of lethal and aggressive prostate cancer [18,110].…”
Section: Could the Dysregulation Of Zinc Transporters Affect Zinc Sup...mentioning
confidence: 99%
“…al. showed that a post-diagnostic low-dose zinc supplementation (1-24 mg/day) in nonmetastatic prostate cancer patients was associated with a lower risk of lethal prostate cancer [109], while high-dose zinc supplementation (>75 mg/day) may increase the risk of lethal and aggressive prostate cancer [18]. Interestingly, a Spanish population of prostate cancer patients receiving zinc supplementation (>10.53 mg/day) may be associated with deleterious effects in those patients with major polygenic risk scores [110], suggesting that a differential effect of zinc supplementation might depend on genetic susceptibility.…”
Section: Could the Dysregulation Of Zinc Transporters Affect Zinc Sup...mentioning
confidence: 99%
“…Molecular and cellular investigations suggest that Se and Zn exhibit reciprocal effects influenced by variations in Zn level [ 22 ]. The low-dose Se and Zn supplementation model can be used to reduce the risk of prostate cancer and overall mortality [ 21 , 23 , 24 ]. However, it should be remembered that supplementation should be performed carefully after studying the level of micronutrients in the patient’s blood/serum.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring the relationship between Zn intake and cancer risk have yielded intriguing and, at times, contradictory ndings. Some reports indicated a positive association between high Zn intake and an increased risk of cancer development [19][20][21][22] , while others have pointed towards potential protective effects of Zn against certain cancer types 23,24 . The exact mechanisms underlying of Zn and its association with cancer progression or regression remain elusive, warranting further investigation into the impact of Zn on tumor growth and immune response.…”
Section: Introductionmentioning
confidence: 99%